Salt tolerant plants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'Saline Agriculture: salt-tolerant plants for developing countries' report of a Panel of the Board on Science and Technology for International Development Office of International Affairs National Research Council, 1990, 70pp ISBN 0 309 04189 9